Notice from the Secretariat of the Congress of Michoacán (Secretaria del Honorable Congreso de Michoacan, 1830)
This is an official notice from the Secretariat of the Congress of Michoacán regarding the acceptance of General of Division Miguel Barragan, constitutionally elected to this Congress